MENGUKUR KINERJA PERUSAHAAN DENGAN BALANCED SCORECARD : Studi Kasus Pada Perusahaan Daerah Air Minum Kota Magelang - Rosyati, Rosyati; Luk, Luk Luk (Jurnal Analisis Bisnis Ekonomi, 2004)
Balance scorecard has a competitive advantage that building strategic management systems now different with traditional management. Implementation in PDAM Magelang expected increase the quality of services, including in non financial. Therefore, PDAM has to measure its performance not only the financial aspect, but also non financial to reach goal congruence. This research reviews the implementation Balance Scorecard in PDAM Magelang. The analysis method using evaluation in performance measurement at four perspectives - financial perspective, costumer perspective, internal bussiness perspective, and innovation and learning perspective. The result shows that financial performance in PDAM Magelang appropriate with financial perspective on BSC. The costumer perspective can not meet 80%, but only 74% suitable with BSC perspective. In internal bussiness perspective suitable as health standard, have no taste, no smell and no color. The innovation and learning perspective can see on employees PDAM Magelang sill not sufficent with BSC perspective. PDAM Magelang must develop its employees like give them opportunity to to get education and increase the grade. Finally, placing its employees congruence with there skill and education.